Immediate implant placement with and without provisionalization: A comparison of a one-year longitudinal study - Po-Sung Fu; Fei-Chi Tseng; Ting-Hsun Lan; Pei-Ling Lai; Cheng-Hwei Chen; Jen-Hao Chen; Chih-Te Liu; Wen-Cheng Chen; Chun-Cheng Hung (Elsevier, 2023)
Background/purpose: Immediate implant placement (IIP) with and without immediate provisionalization (Ipro) may yield satisfactory results in appropriate indications and treatment, especially in the esthetic zone. The aim of this study was to compare implant stability, marginal bone loss (MBL), survival rates, and patient satisfaction between IIP with Ipro and IIP without Ipro. Materials and methods: Seventy patients, each with a failed maxillary anterior tooth, were randomly assigned to IIP with Ipro (Group A: n = 35) or IIP without Ipro (Group B: n = 35). Implant stability quotient (ISQ) and standardized periapical radiographs were performed at surgery and at 3, 6, 9, and 12 months postoperatively to investigate implant stability and MBL, respectively. Survival was assessed 1 year after surgery. Patient satisfaction was evaluated with a visual analogue scale (VAS). Results: Primary ISQ and MBL were not significantly different between groups A and B immediately after surgery (P ＞ 0.05). Implant survival was 100% in both groups, and only one mechanical complication was observed. Patient satisfaction was good at definitive crown delivery and postoperatively 1-year in both groups. However, the immediate postoperative VAS score in Group A was significantly higher than that in Group B (P < 0.05). Conclusion: Group A revealed significantly higher secondary ISQ than Group B at postoperatively 3, 6, 9, and 12 months. There were no significant differences between groups A and B in terms of MBL and survival. Notably, patient satisfaction in Group A was significantly higher than in Group B immediately after surgery.